Young Individuals’ Attitudes Towards Sex Education and Related Factors - Sanlı, Yasemin; Aypar Akbag, Nuran Nur; Arslan, Gamze Goke (Bangladesh Journal of Medical Science, 2023)
Objectives: To determine young individuals’ attitudes towards sexual education and related factors. Emotions, thoughts, and attitudes are as important as knowledge on sexual matters. For this reason, it is necessary to determine the attitudes of young people towards sexual education and the factors affecting these attitudes. Material and Methods: This is a cross-sectional and descriptive study. The study included university students and data were collected via ‘Google Forms’. The study sample is comprised of 501 undergraduate students. We collected the data in November-December 2021 using a Personal Information Form and the Scale of Attitudes towards Sex Education (SATSE). Results: The average SATSE score of the participants was 59.27±11.14. We found that 52.3% of the participants considered their sexual health knowledge level as sufficient, but 60.5% did not receive sexual health education. In addition, it was determined that more than half of the participants could not easily talk about sexual health issues with their families. Conclusion: The results of the research showed that the attitudes of the participants towards sexual education were generally positive. Several characteristics, such as the geographical region resided, father’s education level, being in a romantic relationship, and finding their sexual health knowledge level as sufficient affected their attitudes towards sexual education. Bangladesh Journal of Medical Science Vol. 22 No. 03 July’23 Page : 657-666